2006
DOI: 10.1097/01.ccm.0000198331.45998.85
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in the management of aneurysmal subarachnoid hemorrhage*

Abstract: Many aspects of care in patients with aneurysmal subarachnoid hemorrhage remain highly controversial and warrant further resolution with hypothesis-driven clinical or translational research. It is anticipated that the rigorous evaluation and implementation of such data will provide a basis for improvements in short- and long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 139 publications
0
33
0
2
Order By: Relevance
“…298 -300 Uncontrolled studies using crystalloid or colloid agents suggest that aggressive volume resuscitation can ameliorate the effect of cerebral salt wasting on the risk of cerebral ischemia after aSAH. 301,302 One retrospective study has suggested that 3% saline solution is effective in correcting hyponatremia in this setting. 303 In addition, use of hypertonic saline solution appears to increase regional cerebral blood flow, brain tissue oxygen, and pH in patients with high-grade aSAH.…”
Section: Management Of Medical Complications Associated With Asahmentioning
confidence: 99%
“…298 -300 Uncontrolled studies using crystalloid or colloid agents suggest that aggressive volume resuscitation can ameliorate the effect of cerebral salt wasting on the risk of cerebral ischemia after aSAH. 301,302 One retrospective study has suggested that 3% saline solution is effective in correcting hyponatremia in this setting. 303 In addition, use of hypertonic saline solution appears to increase regional cerebral blood flow, brain tissue oxygen, and pH in patients with high-grade aSAH.…”
Section: Management Of Medical Complications Associated With Asahmentioning
confidence: 99%
“…There are currently 2 publications that we are aware of that have reviewed the current treatments available to prevent cerebral vasospasm in SAH and that mention the potential role for statin therapy. The first review by Naval and colleagues 21 on the different proposed methods of cerebral protection after SAH summarized the current evidence from randomized, controlled trials and retrospective studies that have been conducted on the potential for statins in this role. The second review by Weyer and colleagues 22 was a meta-analytic review of the different treatments that are currently considered for the management of vasospasm after aneurysmal SAH.…”
Section: Sillberg Et Al Do Statins Improve Outcome After Aneurysmal Sah?mentioning
confidence: 99%
“…Early recognition of vasospasm and the potential risk of DIND is essential because the rapid implementation of standard therapies such as triple-H (hypertension, hypervolemia, and hemodilution) therapy, intraarterial vasodilator application, and balloon angioplasty serves to counteract vasospasm and prevent the occurrence of DIND. 24,26,29,38 However, the prompt use of these therapies depends on the ability to predict impending vasospasm or to diagnose it at its early stages.…”
Section: Abstract • Vasospasmmentioning
confidence: 99%
“…Vasospasm can be demonstrated using angiography in approximately 60 to 70% of patients with ruptured aneurysms. 29,31,38 Clinical vasospasm resulting in DIND occurs in 20 to 30% of patients within 3 to 14 days after aneurysmal SAH. Given that vasospasm is the most common cause of morbidity and mortality in patients who survive the initial bleeding episode, it is imperative not only to diagnose the condition but also to predict which patients are likely to become symptomatic.…”
mentioning
confidence: 99%
See 1 more Smart Citation